Terrorism and Economic Growth in Nigeria - Rotimi, Mathew E.; Naphtali, John W.; Irefin, David (ABUAD Journal of Social and Management Sciences, 2024)
Terrorism has emerged as a significant threat to global security and economic stability, with Nigeria experiencing its detrimental effects. This empirical study investigated the relationship between terrorism and economic growth in Nigeria. The study focused on the impact of terrorism on productivity in Nigeria, examining various aspects including economic growth, trade, foreign direct investment (FDI), manufacturing output, and other key indicators but with specific focus on economic growth. It highlighted the pervasive nature of terrorism in Nigeria, with various groups such as Boko Haram, ISIS, Fulani herdsmen, and Niger Delta militants contributing to violence and insecurity. The study reviews both empirical and theoretical literature on terrorism and its economic consequences, emphasizing the negative relationship between terrorism and economic growth. Using a positivist research paradigm, the study employed a Structural Vector Autoregression (SVAR) approach to analyze the impact of terrorism on economic variables in Nigeria. The SVAR model incorporated endogenous variables such as economic growth, capital, terrorism, and trade. Data covering a 42-year period from 1980 to 2021 were utilized, and they were sourced from the World Bank and World Development Indicators. The estimation and results section includes discussions on lag length selection criteria and impulse response analyses to understand the dynamic effects of terrorism on economic variables over time. In conclusion, the study underscored the detrimental impact of terrorism on productivity and economic growth in Nigeria, highlighting the need for effective counter-terrorism measures to mitigate these effects. It provides valuable insights for policymakers and researchers aiming to address the complex challenges posed by terrorism in the country.